2020
DOI: 10.1089/neu.2019.6800
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Cerebral Blood Flow Associated with a History of Concussion

Abstract: Growing evidence suggests that a history of sport concussion may lead to long-term changes in brain physiology, with cerebral blood flow (CBF) being particularly sensitive to injury. However, it is unknown whether these changes are sex specific. The goal of this study was to evaluate sex differences in CBF of asymptomatic athletes, with and without a history of concussion (HOC) using arterial spin labeling (ASL). Scans were acquired for 122 athletes, including those without HOC (33 male, 33 female) and those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 55 publications
4
31
0
Order By: Relevance
“…Nevertheless, the association of the cerebellum with cognitive impairment after mTBI has not been substantially elucidated and needs to be corroborated in future studies. In line with previous findings [8,15], we also identified increased CBF in the bilateral ITG in acute mTBI patients. The ITG is involved in the processes of multimodal sensory integration and visual perception and has been demonstrated volumetric atrophy in mTBI [35].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, the association of the cerebellum with cognitive impairment after mTBI has not been substantially elucidated and needs to be corroborated in future studies. In line with previous findings [8,15], we also identified increased CBF in the bilateral ITG in acute mTBI patients. The ITG is involved in the processes of multimodal sensory integration and visual perception and has been demonstrated volumetric atrophy in mTBI [35].…”
Section: Discussionsupporting
confidence: 93%
“…Using this technique, the alterations of CBF in TBI have been explored in animal models [12] and human studies [13], but few studies focused on mTBI, especially the acute mTBI. Recently, chronic TBI [13] and chronic mTBI [14,15] studies confirmed that the relative disturbances of regional CBF were successfully detected by ASL. Furthermore, Ge et al attempted to evaluate regional CBF changes after chronic mTBI by a resting-state ASL and found significant reductions in mean bilateral thalamic CBF, which was significantly correlated with the simultaneous neuropsychological tests, including measures of learning and memory, response and processing speed, and executive function and verbal fluency [16].…”
Section: Introductionmentioning
confidence: 81%
“…This group also used resting and task-based ASL sequences to detect occipital and temporal hypoperfusion in 2012 in a cohort of 21 moderate-severe TBI patients (27). CBF remains abnormal into the chronic phase (28)(29)(30)(31)(32), and has been associated cognitive performance (27), symptom severity (32) and recovery (30).…”
Section: Introductionmentioning
confidence: 99%
“…In humans it has been proposed that these differences may be related to neck girth (43), hormonal influences (44), and cerebral blood flow and metabolic differences (45). Additionally, recent work by Dumais et al (46) found that males and females have a difference in activation of the default mode network, and the dorsal attention network when exposed to punishment and reward;…”
Section: Discussionmentioning
confidence: 99%